IMPACT OF EMOTIONAL AND SPIRITUAL INTELLEGENCE ON EMPLOYEES OF P. INDOMARCO PRISMATAM SUKADANA EAST LAMPUNG - Rinnanik Rinnanik; Hikmatul Aliyah; Sri Rahayu; Leni Citra Handayani (Journal of Research in Social Science and Humanities, 2024)
The aim of this research is to find out the impact of emotional and spiritual intelligence on employee performance. The data gathering techniques in this study are done with observations, interviews, questionnaires, and documentation. The population in this study was selected based on the total number of employees of a total of 28 employees at PT Indomarco Prismatama Sukadana East Lampung. In this study, the researchers used saturated sampling. Based on the results of the calculation of the test t through the coefficients table obtained variable significance values of X1 of 0.017 and X2 of 0.019. While simultaneously, through the anova table known significance of 0.003 is a small result of 0.05 which means Ha3 accepted that there is an influence of emotional intelligence and spiritual intelligence on the performance of employees in PT Indomarco Prismatama Sukadana East Lampung. The regression equation result is Y = 3.542 + 0.451 X1 + 0.381 X2, whereas R counts 0.611, which means that the degree of relationship between emotional intelligence (X1) and spiritual intelligences (X2) with employee performance (Y) is quite strong. Whereas the R squere value is 0.373, R Squere can be called a determination coefficient in this case, meaning that the regression model method can be used to predict the Y variable which means Emotional Intelligence and Spiritual Intelligence influence employees performance by 37.3% and the rest is influenced by other factors.